Imaging Features of Bilateral Slipped Upper Femoral Epiphysis in Sequential Presentation of Hip Pain: A Case Report - Chandrashekar Patil; Rithya Kuppam; Akhila Bandaru; Nikhitha Mangalagiri; B Vasudha (International Journal of Anatomy Radiology and Surgery)
Slipped Upper Femoral Epiphysis (SUFE) is the most common hip abnormality in adolescents, leading to significant morbidity if not properly treated. It is classified as a Salter-Harris type I injury, resulting from a fall that affects the physis of both hips and can cause unstable alignment between the epiphysis and metaphysis. They typically present with a decreased range of motion, hip discomfort and limping. Hereby, the author presents the case of 12-year-old adolescent female with a sequential history of hip pain one after the other after a fall one month back. On physical examination, full internal rotation was lacking and flexion and abduction ability were limited. X-ray and Magnetic Resonance Imaging (MRI) of both hip joints were taken, which revealed widened epiphysis of bilateral femurs with slippage of bilateral femoral epiphysis onto metaphysis, suggestive of bilateral SUFE. Later the patient underwent bilateral prophylactic in-situ fixation with screws to prevent further slippage and long-term complications.